Manufacturing industry performance and stabilisation policies in South Africa - Desiree L. Hunter; Asrat Tsegaye; Forget M. Kapingura (South African Journal of Economic and Management Sciences)
Background: Manufacturing performance in South Africa is concerning, with the sector displaying signs of early deindustrialisation. South African authorities use a strategic blend of stabilisation policies in managing these unique macroeconomic conditions.